2016
DOI: 10.1097/iae.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Related Quality of Life and Visual Function After Retinal Detachment Surgery

Abstract: The vision-related quality of life is significantly impaired in patients after surgery for RRD. Higher age and female gender negatively influences the results of the composite score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Most clinical studies use BCVA as the single visual outcome measure because it is considered to be the major determinant of vision-related quality of life. 23 However, the current study supports the idea that merely measuring BCVA inadequately evaluates vision-related quality of life and visual function in patients after surgery for macula-off RRD. This idea is also supported by Lina et al, 7 who investigated three visual function parameters (BCVA, stereopsis and metamorphopsia) and found that vision-related quality of life correlated with metamorphopsia, but not with BCVA.…”
Section: Discussionsupporting
confidence: 60%
“…Most clinical studies use BCVA as the single visual outcome measure because it is considered to be the major determinant of vision-related quality of life. 23 However, the current study supports the idea that merely measuring BCVA inadequately evaluates vision-related quality of life and visual function in patients after surgery for macula-off RRD. This idea is also supported by Lina et al, 7 who investigated three visual function parameters (BCVA, stereopsis and metamorphopsia) and found that vision-related quality of life correlated with metamorphopsia, but not with BCVA.…”
Section: Discussionsupporting
confidence: 60%
“…Studies determining the vision-related quality of life in people with ocular chemical injury revealed that ocular chemical burns have a significant and negative impact on a broad array of vision-related quality of life: visual acuity, physical function, and social function 5 . The quality of life of patients with chemical burns was also found to be significantly lower than that reported in other ocular diseases 6 . Ocular pain is very common in those patients and has significantly long-lasting effects on the patient's quality of life.…”
Section: Introductionmentioning
confidence: 52%
“…Retinal detachment (RD), the separation of the neural retina from the underlying retinal pigment epithelium (RPE), is a well-known cause of visual loss and has a major impact on quality of life 1 . Although the retina can be reattached by various surgical procedures, the final visual outcome is often unsatisfactory [2][3][4][5][6][7][8] .…”
mentioning
confidence: 99%